RNA-Seq Reveals Different Gene Expression in Liver-Specific Prohibitin 1 Knock-Out Mice - Lee, Kyuwon; Yu, Hyeonju; Shouse, Stephanie; Kong, Byungwhi; Lee, Jihye; Lee, Seong-Ho; Ko, Kwang Suk (Frontiers in Physiology, 2021)
Prohibitin 1 (PHB1) is an evolutionarily conserved and ubiquitously expressed protein that stabilizes mitochondrial chaperone. Our previous studies showed that liver-specific Phb1 deficiency induced liver injuries and aggravated lipopolysaccharide (LPS)-induced innate immune responses. In this study, we performed RNA sequencing (RNA-seq) analysis with liver tissues to investigate global gene expression among liver-specific Phb1-/-, Phb1+/- and WT mice, focusing on the differentially expressed (DE) genes between Phb1+/- and WT. Results indicated that 78 DE genes were identified in the comparison between Phb1+/-and WT. Both upstream and causal network regulators analyses revealed that insulin receptor (Insr), sterol regulatory element-binding transcription factor 1 (Srebf1), Srebf2, SREBP cleavage-activating protein (Scap) were predicted to be significant in liver-specific Phb1+/- compared to WT. Of diseases and biofunctions, hepatic system diseases were ranked as the second, followed by organismal injuries and abnormalities. Hepatotoxicity pathways included liver fibrosis, liver hyperplasia/hyperproliferation, liver necrosis/cell death. Interestingly, of liver diseases-related 5 DE genes between Phb1+/- and WT, the mRNA expressions of forkhead box M1 (Foxm1) and TIMP inhibitor of metalloproteinase (Timp1) were matched with validation for RNA-seq in liver tissues and AML12 cells transfected with Phb1 siRNA. The results in this study provide additional insights into molecular mechanisms responsible for increasing susceptibility of liver injuries associated with hepatic Phb1.